2000
DOI: 10.1074/jbc.m005287200
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 Regulates Stress-induced, Redox-dependent Heat Shock Factor Activation

Abstract: The signaling pathway by which environmental stresses activate heat shock factors (HSFs) is not completely understood. We show that the small GTPase rac1, and Rac1-regulated reactive oxygen species (ROS) play an important role in stress-stimulated heat shock response. A dominant-negative allele of Rac1 (Rac1N17) inhibits the hypoxia/reoxygenation and sodium arsenite-induced transcriptional activity of HSF-1 and the transcription of heat shock protein 70. Rac1N17 also suppresses the production of intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 45 publications
6
53
0
1
Order By: Relevance
“…A constitutively active Rac1 mutant does not increase intracellular ROS. Rac1 GTPase is, therefore, a necessary but not sufficient component of the pathway leading to ROS production during reoxygenation (87).…”
Section: Nadph Oxidasementioning
confidence: 99%
“…A constitutively active Rac1 mutant does not increase intracellular ROS. Rac1 GTPase is, therefore, a necessary but not sufficient component of the pathway leading to ROS production during reoxygenation (87).…”
Section: Nadph Oxidasementioning
confidence: 99%
“…The insight gained from characterization of the neutrophil NADPH oxidase system prompted several laboratories to address whether analogous systems existed in nonphagocytic cells. Evidence that a nonphagocytic NADPH oxidase existed was bolstered by the observation that expression of constitutively activated forms of Rac1 was capable of increasing intracellular ROS levels in a variety of nonphagocytic cells (10)(11)(12)(13)(14)(15). In addition, a dominant negative form of Rac1 was shown to be able to block ROS production from a number of different cytokines or growth factors (10).…”
mentioning
confidence: 99%
“…Rac proteins, in particular rac1, function similarly in nonphagocytic cells, 1,12 and such rac1-regulated ROS have been implicated in a variety of cellular processes including growth, migration, and transformation. 2,8,[12][13][14][15][16][17] We have recently shown that rac1-regulated ROS production also mediates apoptosis in response to I/R. 7 Hepatocyte growth factor (HGF), which was initially isolated as a potent mitogen for hepatocytes, is now known to be a broad-spectrum mitogen for a variety of cell types.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] There are accumulating data indicating that regulation of the intracellular redox state is a versatile control mechanism in signal transduction in both pathological and physiological conditions. 6 Ischemia/reperfusion (I/R) and hypoxia/reoxygenation (H/ R) result in the production of ROS within tissue or cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation